The Role of Extracurricular Activities in Psychological Resilience Development Among Primary Class Students from their Teacher’s Point of View in Private Schools in Amman Governorate - Al-Raqqad, Hana’a Khaled; Bushnaq, Suzan Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the role of extracurricular activities in psychological resilience development among students in basic grades in private schools from the point of view of their teachers in the capital city of Amman, as well as to find out of differences between estimations means of primary grades teachers contribution extent of extracurricular activities in psychological resilience development due to (Gender, academic qualification, and years of experience). In order to achieve study objectives, descriptive analytical methodology was used. The research also used psychological resilience scale. The research sample consisted of 273 male and female students. In order to answer the research questions, different statistical techniques were used through the (SPSS), Social Packaging Statistical System. The research concluded that there is a role of extra-curricular activities in psychological resilience level with a mean(2.33 out 3 ). The research results indicated that there are no differences in extra-curricular activities roles in the role of extra-curricular activities in the physical resilience to gender.The results also indicated that there differences in extra-curricular activities role in psychological resilience, due to variables (educational level, gender, years of experience, and age). The study recommended a set of recommendations.
Keywords: Extracurricular Activities; Psychological Resilience; Primary Classes; Private Schools